2014
DOI: 10.1037/a0035931
|View full text |Cite
|
Sign up to set email alerts
|

An eye for an eye? Exploring the relationship between workplace incivility experiences and perpetration.

Abstract: We examined the effects of gender and organizational climate for incivility on the relationship between individuals' incivility experiences and perpetration. Based on Andersson and Pearson's (1999) concept of the incivility spiral, Naylor, Pritchard, and Ilgen's (1980) theory of behavior in organizations, and social interactionist theory (Felson & Tedeschi, 1993), we proposed an interaction between incivility experiences, organizational climate for incivility (organizational tolerance and policies), and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
97
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 64 publications
7
97
0
Order By: Relevance
“…Men were found to report uncivil behavior more often, both on an interpersonal level and also on an organizational level (Reio & Ghosh, 2009). Consistent with this, Gallus et al (2014) found that men were more likely than women to engage in uncivil conduct. Reio and Ghosh (2009) showed that young men were the most likely instigators of workplace incivility.…”
Section: Prevalence Of Incivilitysupporting
confidence: 74%
See 2 more Smart Citations
“…Men were found to report uncivil behavior more often, both on an interpersonal level and also on an organizational level (Reio & Ghosh, 2009). Consistent with this, Gallus et al (2014) found that men were more likely than women to engage in uncivil conduct. Reio and Ghosh (2009) showed that young men were the most likely instigators of workplace incivility.…”
Section: Prevalence Of Incivilitysupporting
confidence: 74%
“…Some support has been shown for this theory, as Porath and Pearson (2012) found that being targeted by aggressive behavior relate, indirectly via anger and fear, to negative behaviors aimed at the instigator. One study directly ties incivility experiences to incivility perpetration among both men and women (Gallus et al, 2014). However, Pearson et al (2001) found support for the hypothesis that merely witnessing incivility is related to a need to retaliate on behalf of the target, indicating that uncivil conduct can reach beyond the victim.…”
Section: Negative Outcomes Of Experienced and Witnessed Incivilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Thus incivility is subjective in nature and therefore each one of the parties to an uncivil encounter can interpret reality in a different manner, which eventually leads to differences in attribution of intent. While some targets of incivility perceive it as intended, others might not consider it as intended (Gallus et al 2014;Sliter et al 2012).…”
Section: Incivilitymentioning
confidence: 97%
“…Being targeted by incivility robs targets of felt power; they often seek to regain power by enacting incivility toward others (Gallus, Bunk, Matthews, Barnes-Farrell, & Magley, 2014). A recent line of research shows that these kinds of norm violations are means of expressing and gaining power.…”
Section: Incivility As Status Challengementioning
confidence: 99%